1970
DOI: 10.1042/bj1190629
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid requirement for the growth-hormone stimulation of incorporation of precursors into protein and nucleic acids of liver slices

Abstract: 1. Incorporation of [(14)C]leucine into protein in rat liver slices, incubated in vitro, increased as the concentration of unlabelled amino acids in the incubation medium was raised. A plateau of incorporation was reached when the amino acid concentration was 6 times that present in rat plasma. Labelling of RNA by [(3)H]orotic acid was not stimulated by increased amino acid concentration in the incubation medium. 2. When amino acids were absent from the medium, or present at the normal plasma concentrations, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

1971
1971
2001
2001

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…The effect of cholestasis on leucine incorporation seems thus to be quite independent of amino acid content in the media, in contrast to, for example, the absolute dependence on amino acids for growth hormone stimulation of protein synthesis in liver slices [9]. The free soluble ra dioactivity was similar in control and cholestatic material.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The effect of cholestasis on leucine incorporation seems thus to be quite independent of amino acid content in the media, in contrast to, for example, the absolute dependence on amino acids for growth hormone stimulation of protein synthesis in liver slices [9]. The free soluble ra dioactivity was similar in control and cholestatic material.…”
Section: Discussionmentioning
confidence: 77%
“…Part of this difference may be due to a continuous decrease of the spe cific activity of the precursor pool because of protein degradation. A contributory factor may also be that for 3H-leucine, a larger proportion of the free radioactivity is located in water and metabolites of amino ac ids [5], The higher rate of leucine incorporation in medium 2 compared to medium 1 seems to be due mainly to the higher concentration of leu cine in medium 2 [9]. There is little indication that the amino acid mix ture modifies the increase in leucine incorporation between 0.05 itim (medium 1) and 0.5 mM (medium 2) leucine concentration in the medi um.…”
Section: Discussionmentioning
confidence: 99%
“…The present results are relevant to the observed amino acid requirement for an enhancement of protein synthesis by growth hormone in the incubated liver-slice system (Clemens & Korner, 1970). The hormone may stimulate translation by increasing the availability ofamino acids to the protein-synthesizing complex, or alternatively a high concentration of amino acids may be necessary in order that ribosomal activity is not already rate-limiting.…”
mentioning
confidence: 69%
“…until death or starved overnight (16h). The tissue was incubated for 1 h in a medium containing either normal plasma concentrations of 20 amino acids or six times these concentrations (Clemens & Korner, 1970). Post-mitochondrial supernatants, ribosomes and cell sap were prepared from the slices and from unincubated liver, and cell-free amino acid incorporation was assayed as described by Clemens & Korner (1971).…”
mentioning
confidence: 99%
“…The relationship of amino acids to the mechanism of action of growth hormone Jefferson & Korner (1967) and Clemens & Korner (1970) have shown that growth hormone stimulates directly the labelling of protein and RNA in perfused liver or liver slices from normal rats, but only when amino acids are present in the medium at three or six times plasma levels. These results suggest that the protein synthetic ability of the liver may be limited unless amino acids are in plentiful supply.…”
Section: The Relationship Of Polysomes To Protein Synthesismentioning
confidence: 99%